Panorama dos estudos das vogais pretônicas no Português do Brasil - Oliveira Chaves, Idalena (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article is part of my doctoral thesis, defended in 2013, oriented by prof.Dr.Seung Hwa Lee. Investigate the results of the analysis of research masters and doctoral level in the period 1980-2012, about middle vowels in pretonic position in Brazilian Portuguese, which now take place as [e i] e [o u] in various dialects of Brazil. The research was supported by a methodology called Synthesis Research (NORRIS and ORTEGA, 2006) and the statistical feature of the meta-analysis (GLASS, 1977). I discuss the results of investigations on the pretonic vocalism that had to support the theory of variation, referenced by William Labov, in the 60s and 70s 28 dissertations and 10 doctoral theses were used as references, covering almost all regions of Brazil.